Application of non-contact scanning to forensic podiatry: A feasibility study. Issue 1 (January 2021) - Crowther, Matthew; Reidy, Selina; Walker, Jeremy; Islam, Meez; Thompson, Tim
Highlights: The study introduces 3D data capture to the analysis of insoles in a forensic context. The study compares three different modes of data capture when using the Gunn methods. Five of the six measurements of the Gunn method differed significantly between the three modes. Further investigations need to be conducted on the use of 3D scanners to Forensic Podiatry. Abstract: Foot impression evidence recovered from crime scenes can be available in the form of barefoot prints, sock-clad footprints, or as impressions within footwear. In some cases, suspects leave their footwear at the scene of the crime, and the insoles from the footwear can be important in linking a person to the footwear. The application of 3D data-collecting technology is becoming more and more popular within forensic science and has been used to recover footwear impression evidence. The present study is a feasibility study to discover if 3D data capturing devices can be applied to insoles; to capture the footprint impression for measurement using the Gunn method (a method used in forensic podiatry casework). Three different methods of data capture were conducted; Adobe Photoshop, MeshLab, and calipers used directly on the insole. Paired t-tests and Intraclass Correlation Coefficient (ICC) were conducted for all three data capture methods. Seven measurements used in this study were significantly different across all three methods. ICC scores were moderate to excellent for the Photoshop method, poor to good for the 3D method, and moderate to excellent for the Direct method.